Multifluid modeling of the desulfurization process within a bubbling fluidized bed coal gasifier - Armstrong, L-M.; Gu, Sai; Luo, K. H.; Mahanta, P. (John Wiley & Sons, Ltd, 2013)
The desulfurization process to a two-dimensional (2-D) and three-dimensional (3-D) Eulerian-Eulerian computational fluid dynamic (CFD) model of a coal bubbling fluidized gasifier is introduced. The desulfurization process is important for the reduction of harmful SOx emissions; therefore, the development of a CFD model capable of predicting chemical reactions involving desulfurization is key to the optimization of reactor designs and operating conditions. To model the process, one gaseous phase and five particulate phases are included. Devolatilization, heterogeneous, and homogeneous chemical reactions as well as calcination and desulfurization reactions are incorporated. A calcination-only model and a calcination plus desulfurization model are simulated in 2-D and 3-D and the concentrations of SO2 leaving the reactors are compared. The simulated results are assessed against available published experimental data. The influence of the fluidized bed on the desulfurization is also considered.